2012
DOI: 10.3109/10826084.2012.663296
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Co-Morbidity and Substance Use Disorders: Treatment in Parallel Systems or in One Integrated System?

Abstract: Psychiatric co-morbidity among substance users refers to the simultaneous presence of at least another psychiatric disorder in a person diagnosed with a substance use disorder. Co-morbid patients represent a substantial number of people in treatment and present greater disorder severity from both the clinical and social perspectives than those people diagnosed with only one type of disorder. We present an overview of the current state of the art concerning the choice of site of treatment, the kind of intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 72 publications
3
56
0
14
Order By: Relevance
“…Moreover, by identifying an unambiguous environmental explanation to a risk factor of AUD, this study builds on our program research, which has focused on the course of AUD from drinking onset to midlife (Jacob et al, 2005(Jacob et al, , 2010(Jacob et al, , 2012. Although these fi ndings alone are insuffi cient to demonstrate a clear genetic or environmental interpretation regarding correlates of problem drinking, they highlight the potential value of integrated interventions for comorbidity to address problem drinking among individuals in midlife (Drake et al, 2008;Torrens et al, 2012). Specifi cally, these fi ndings suggest that co-occurring psychiatric symptoms may exert a direct effect on the risk of problem drinking in midlife that is not mediated by shared genetic risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by identifying an unambiguous environmental explanation to a risk factor of AUD, this study builds on our program research, which has focused on the course of AUD from drinking onset to midlife (Jacob et al, 2005(Jacob et al, , 2010(Jacob et al, , 2012. Although these fi ndings alone are insuffi cient to demonstrate a clear genetic or environmental interpretation regarding correlates of problem drinking, they highlight the potential value of integrated interventions for comorbidity to address problem drinking among individuals in midlife (Drake et al, 2008;Torrens et al, 2012). Specifi cally, these fi ndings suggest that co-occurring psychiatric symptoms may exert a direct effect on the risk of problem drinking in midlife that is not mediated by shared genetic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the fi ndings highlight the importance of AUD interventions to monitor and address co-occurring psychiatric disorders for individuals in midlife. Such an integrated treatment approach has received increasing recognition in the substance use disorder treatment community (Drake et al, 2008;Torrens et al, 2012). Moreover, prior research has suggested that for dual-diagnosis patients (i.e., individuals with co-occurring substance use and psychiatric disorders), enhancement of general, as well as substance-specifi c, coping skills is needed to improve long-term functioning (Moggi et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Apesar disso, historicamente, as políticas públicas em saúde mental dividem as ofertas de tratamentos em dois tipos de serviços: aqueles que atendem pessoas com diagnósticos de transtornos mentais e aqueles que oferecem tratamento para problemas com o consumo de drogas (TORRENS et al, 2012), sendo essa a realidade encontrada em diversos países GINGERICH, 2013), inclusive no Brasil. Aponta-se a importância de reunir esforços para construir intervenções conjuntas para a condição (ROSENBLUM et al, 2014) e sugere-se que seja feita identificação e avaliação da comorbidade, tanto nos serviços de tratamento do consumo problemático de drogas, como nos serviços de saúde mental (CORRADI-WEBSTER; LAPREGA; FURTADO, 2009).…”
unclassified
“…La depresión también tiene un impacto negativo en el tratamiento del TUS: los pacientes dependientes de alcohol con depresión mayor tienen más probabilidad de recaídas, los dependientes de cocaína con depresión mayor tienen peores resultados en la terapia cognitivo-conductual y los síntomas depresivos predicen el uso futuro de estimulantes (Worley et al, 2012). Más aún, el estado de ánimo deprimido es frecuentemente citado como precipitante de la recaída entre los sujetos con TUS López-Muñoz, Álamo et al, 2010;Rosenberg et al, 2001), patología cardiovascular, hepática y gastrointestinal (Horsfall et al, 2009), mayor comorbilidad orgánica general (Torrens, Rossi, Martínez-Riera, Martínez-Sanvisens y Bulbena, 2012), mayores tasas de desempleo y marginación (Caton et al 1994; Vázquez, Muñoz y Sanz, 1997) y mayor probabilidad de llegar a ser sin techo (Tsuang y Fong, 2004).…”
Section: 3-consecuencias De La Pdunclassified
“…Debido a las complejas características clínicas de los pacientes con PD, es necesario un enfoque multidisciplinar que aúne las perspectivas psicopatológica, médica y social (Torrens et al, 2012).…”
Section: 5-evaluación De La Pdunclassified